Magnetic Resonance Imaging after Translabyrinthine Complete Excision of Vestibular Schwannomas - Tysome, James R.; Moffat, David A. (Journal of Neurological Surgery Part B: Skull Base, 2012)
The objective of this study is to determine whether magnetic resonance imaging (MRI) at 2 years following complete vestibular schwannoma (VS) excision using a translabyrinthine approach is sufficient to detect recurrent tumor. The study is set in a tertiary referral skull base unit. A service evaluation of a prospective database identified patients who underwent complete translabyrinthine VS excision with prospectively recorded MRI results at 2 and 5 years following surgery. The main outcome measures were evidence of tumor recurrence on MRI at 2 and 5 years after surgery. Of 314 patients in the study, all patients where MRI was reported to show no recurrence at 2 years (97%) also had no signs of recurrence on MRI at 5 years. All eight patients with MRI suspicious of recurrence (linear enhancement of internal auditory canal [IAC]) at 2 years had no progression on MRI at 5 to 15 years. One patient had evidence of definite recurrence (nodular enhancement of IAC) at 2 years, who went on to have radiosurgery at 8 years. Where patients have MRI with no linear enhancement of the IAC at 2 years, no further imaging is required. Where linear enhancement is seen, no change in enhancement at 5 years is reassuring and no further imaging is required.
Keywords: vestibular schwannoma; magnetic resonance imaging; follow-up studies; postoperative period